Concepts and Coefficients Based on John L. Holland’s Theory of Vocational Choice—Examining the R Package holland - Florian G. Hartmann; Jörg-Henrik Heine; Bernhard Ertl (Psych, 2021)
John L. Holland’s theory of vocational choice is one of the most prominent career theories and is used by both researchers and practitioners around the world. The theory states that people should seek work environments that fit their vocational interests in order to be satisfied and successful. Its application in research and practice requires the determination of coefficients, which quantify its core concepts such as person-environment fit. The recently released R package holland aims at providing a holistic collection of the references, descriptions and calculations of the most important coefficients. The current paper presents the package and examines it in terms of its application for research and practice. For this purpose, the functions of the package are applied and discussed. Furthermore, recommendations are made in the case of multiple coefficients for the same theoretical concept and features that future releases should include are discussed. The R package holland is a promising computational environment providing multiple coefficients for Holland’s most important theoretical concepts.